Recent Progress of Electrode Materials for Flexible Perovskite Solar Cells - Xu, Yumeng; Lin, Zhenhua; Wei, Wei; Hao, Yue; Liu, Shengzhong; Ouyang, Jianyong; Chang, Jingjing (Nano-Micro Letters, 2022)
Flexible perovskite solar cells (FPSCs) have attracted enormous interest in wearable and portable electronics due to their high power-per-weight and low cost. Flexible and efficient perovskite solar cells require the development of flexible electrodes compatible with the optoelectronic properties of perovskite. In this review, the recent progress of flexible electrodes used in FPSCs is comprehensively reviewed. The major features of flexible transparent electrodes, including transparent conductive oxides, conductive polymer, carbon nanomaterials and nanostructured metallic materials are systematically compared. And the corresponding modification strategies and device performance are summarized. Moreover, flexible opaque electrodes including metal films, opaque carbon materials and metal foils are critically assessed. Finally, the development directions and difficulties of flexible electrodes are given. Highlights: 1 Convincing candidates of flexible transparent electrodes are discussed in detail from the views of fabrication, properties and device performance. 2 The progresses of flexible opaque electrodes used in flexible perovskite solar cells are provided. 3 The future directions and challenges in developing flexible electrodes are highlighted.